Perlindungan Hukum Korban Kekerasan dalam Rumah Tangga di Indonesia: Analisis Undang-Undang Nomor 23 Tahun 2004 (International Forum of Researchers and Lecturers, 2024)
Domestic violence is a critical and increasing issue in Indonesia, as recorded by the National Commission on Violence Against Women. The government has addressed this issue by enacting Law Number 23 of 2004 on the Elimination of Domestic Violence (UU KDRT). This study aims to analyze the legal protections provided to DV victims under the law, identify implementation challenges, and evaluate improvement efforts. Using a qualitative approach with normative juridical methods, the research examines the provisions of UU KDRT and its practical application. The findings reveal that despite comprehensive protections, barriers such as patriarchal culture, social stigma, and limited protective infrastructure significantly hinder effectiveness. Policy reform, capacity building for law enforcement, and strengthening victim support infrastructure are proposed as key strategies. The study highlights the importance of cross-sectoral synergy to enhance the implementation of UU KDRT and ensure more effective legal protection for DV victims.